Bridges to recovery addiction, family therapy, and multicultural treatment - Krestan, Jo-Ann (Free Press, 2000)
"Bridges to Recovery is the first book to bring together experts from three major fields within psychotherapy - family therapy, addiction counseling and multicultural treatment - to provide a framework for working with families within their individual cultural contexts. Drawing upon case studies, clinical anecdotes and proven treatment methods, Bridges to Recovery provides practitioners with insight into the individual cultural nuances that make addiction recovery a personal journey." "This book will be an asset to teachers and students in clinical social work, psychology and substance abuse counseling programs."--Jacket.